Importance of Contextualizing Islamic Religious Education in Social Transformation Era - Sobirin, Moh.; Djubaedi, Dedi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2024)
This study seeks to contextualize Islamic Religious Education and its significance in addressing the era of social transition. This study employs a qualitative methodology utilizing library research. Data gathering methods involve sourcing information from notes, transcripts, books, scientific journals, articles, papers, websites, documents, and scholarly works pertinent to the topic of discussion. Data analysis techniques employ content analysis, a scientific method for examining and deriving conclusions from documents or texts. The study's results indicate that contextualization involves situating an element within its context, thereby enhancing comprehension beyond mere literal interpretations to encompass the impact of historical, cultural, psychological, and political circumstances surrounding the text's inception. Contextual comprehension is crucial in addressing issues that emerge from significant societal transformations in the contemporary day. This urgency is evident in the objectives and functions of contextualizing Islamic Religious Education. Contextualization seeks to foresee contemporary issues, forecast meanings deemed pertinent for the future, and establish the relationship between the text of the Qur'an and its applications. The purpose of contextual knowledge is to elucidate the meaning of religious writings foundational to Islamic Religious Education, safeguard against misinterpretations, facilitate novel interpretations, and provide solutions to navigate the complexities inherent in religious texts.